Pelatihan Administrasi Pemerintahan Desa Kertayasa Kecamatan Sidangagung Menggunakan Microsoft Office - Heru Budianto; Fitra Nugraha; Aji Permana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Kuningan, 2025)
Orderly administration is a must for government managers, from the smallest government unit to the highest. The role of village officials is highly expected in creating dynamic institutions and adaptive village culture. However, this is not the case in Kertayasa Village, Sindangadung District, Kuningan Regency, administrative services are still hampered due to missing, damaged or scattered records. Therefore, training in the use of technology (in this case Microsoft Office applications) is needed to support the tasks of village officials and ensure orderly management. This service activity focuses on village officials to improve their skills in mastering technology and applications to support daily work. This event is for social networking and training and lasts for 1 day. The output of this training is publication in the accredited service journal